Accuracy of chimeric proteins in the serological diagnosis of chronic chagas disease - a Phase II study. - Fred Luciano Neves Santos; Paola Alejandra Fiorani Celedon; Nilson Ivo Tonin Zanchin; Wayner Vieira de Souza; Edimilson Domingos da Silva; Leonardo Foti; Marco Aurélio Krieger; Yara de Miranda Gomes (Public Library of Science (PLoS), 2017)
BACKGROUND:The performance of current serologic tests for diagnosing chronic Chagas disease (CD) is highly variable. The search for new diagnostic markers has been a constant challenge for improving accuracy and reducing the number of inconclusive results. METHODOLOGY/PRINCIPAL FINDINGS:Here, four chimeric proteins (IBMP-8.1 to -8.4) comprising immunodominant regions of different Trypanosoma cruzi antigens were tested by enzyme-linked immunosorbent assay. The proteins were used to detect specific anti-T. cruzi antibodies in the sera of 857 chagasic and 689 non-chagasic individuals to evaluate their accuracy for chronic CD diagnosis. The antigens were recombinantly expressed in Escherichia coli and purified by chromatographic methods. The sensitivity and specificity values ranged from 94.3% to 99.3% and 99.4% to 100%, respectively. The diagnostic odds ratio (DOR) values were 6,462 for IBMP-8.1, 3,807 for IBMP-8.2, 32,095 for IBMP-8.3, and 283,714 for IBMP-8.4. These chimeric antigens presented DORs that were higher than the commercial test Pathozyme Chagas. The antigens IBMP-8.3 and -8.4 also showed DORs higher than the Gold ELISA Chagas test. Mixtures with equimolar concentrations were tested in order to improve the diagnosis accuracy of negative samples with high signal and positive samples with low signal. However, no gain in accuracy was observed relative to the individual antigens. A total of 1,079 additional sera were used to test cross-reactivity to unrelated diseases. The cross-reactivity rates ranged from 0.37% to 0.74% even for Leishmania spp., a pathogen showing relatively high genome sequence identity to T. cruzi. Imprecision analyses showed that IBMP chimeras are very stable and the results are highly reproducible. CONCLUSIONS/SIGNIFICANCE:Our findings indicate that the IBMP-8.4 antigen can be safely used in serological tests for T. cruzi screening in blood banks and for chronic CD laboratory diagnosis.